Impact of Exports, Imports, Foreign Direct Investment, and Government Expenditure on the Economic Growth of Nepal - Devkota, Sunil (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Nepal is undergoing a phase of trade deficit as the economy is massively dependent on imports with few exports and insignificant foreign direct investment. This study was made to assess the impact of exports, imports, foreign direct investment, and government expenditure on the economic growth of Nepal and to determine the level of impact.Methodology: The dependent variable was economic growth represented by gross domestic product and the independent variables were the exports, imports, foreign direct investments, and government expenditure. Data on dependent and independent variables were collected from secondary sources for the period 2000 to 2022. The collected data was analyzed in SPSS by employing the Ordinary Least Square method and Linear Regression. A regression model was formulated to explain economic development. Findings andConclusion: The analysis showed that exports have a significant impact on economic growth, however in the opposite direction. The foreign direct investment did not have any impact on the economic development of Nepal as the p-value was greater than 0.05, and government expenditure has a positive relationship with economic growth however the degree of association was not significant.Implications: The findings of the research provide insights into the variables of economic development and may be referred to for crafting development strategies. The results emphasize the complex nature of factors influencing economic development, suggesting the need for policy interventions and further research to fully understand the dynamics at play. Future studies should consider including more variables in the model and analyzing the impact on economic growth to make the research more effective.